Investigating customer loyalty: can fast-food restaurants keep them coming back? / Mohd Aliff Abdul Majid ... [et al.] - Abdul Majid, Mohd Aliff; Azman, Ana Batrisyia; Mohd Zaki, Mohd Izwan; Zahari, Harnizam; Hassan, Hafizah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
In the realm of fast-food restaurants, the primary objective revolves around the establishment and nurturing of customer loyalty. This loyalty holds the potential to significantly impact the long-term sustainability and profitability. This study seeks to investigate the factors contributing to the development of customer loyalty within fast-food restaurants. A quantitative research approach was employed, and a questionnaire was utilized to investigate the influence of specific factors, focusing on restaurant atmosphere, food quality, and service quality, in enhancing customer loyalty within fast-food establishments located in Kuala Terengganu, Malaysia. Data collection was carried out through convenience sampling, involving 150 respondents, and the collected data underwent analysis through multiple regression techniques. The outcomes of this study clearly underscore the pivotal role played by service quality in shaping customer loyalty within the context of fast-food restaurants. Consequently, it is evident that further research endeavours, incorporating additional data and broader perspectives, are imperative to provide a more comprehensive understanding of the multifaceted factors that wield influence over customer loyalty in fast-food restaurants. This research aspires to provide empirical insights that can empower both scholars and industry professionals to formulate finely tuned marketing and operational strategies aimed at optimizing customer loyalty within the fast-food sector.